Qualitative Research in Emergency Care Part I: Research Principles and Common Applications. (18th August 2015) - Choo, Esther K.; Garro, Aris C.; Ranney, Megan L.; Meisel, Zachary F.; Morrow Guthrie, Kate; Newgard, Craig
Abstract Qualitative methods are increasingly being used in emergency care research. Rigorous qualitative methods can play a critical role in advancing the emergency care research agenda by allowing investigators to generate hypotheses, gain an in‐depth understanding of health problems or specific populations, create expert consensus, and develop new intervention and dissemination strategies. This article, Part I of a two‐article series, provides an introduction to general principles of applied qualitative health research and examples of its common use in emergency care research, describing study designs and data collection methods most relevant to our field, including observation, individual interviews, and focus groups. In Part II of this series, we will outline the specific steps necessary to conduct a valid and reliable qualitative research project, with a focus on interview‐based studies. These elements include building the research team, preparing data collection guides, defining and obtaining an adequate sample, collecting and organizing qualitative data, and coding and analyzing the data. We also discuss potential ethical considerations unique to qualitative research as it relates to emergency care research.